2022
DOI: 10.1097/rlu.0000000000004480
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 68Ga-FAPI-04 PET/CT on Staging and Therapeutic Management in Patients With Digestive System Tumors

Abstract: We aimed to determine the impact of fibroblast activation protein inhibitor (FAPI)-directed molecular imaging on staging and therapeutic management in patients affected with digestive system tumors when compared with guideline-compatible imaging (GCI). Patients and Methods: Thirty-two patients with tumors of the digestive system were included: colon adenocarcinoma, 2/32 (6.3%); hepatocellular carcinoma (HCC), 6/32 (18.8%); pancreatic duct adenocarcinoma (PDAC), 6/32 (18.8%), and gastroenteropancreatic neuroend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(107 citation statements)
references
References 43 publications
6
97
4
Order By: Relevance
“…As such, even in those patients with aggressive disease, the use of CXCR4-targeted PET/CT should be omitted and cannot replace current standard imaging. In this regard, a recent study demonstrating that fibroblast activation protein inhibitory PET/CT may provide an additional benefit, in particular, for PDAC and HCC 16 . Those considerations are further fueled by a recent report exclusively investigating PDAC, also demonstrating that fibroblast activation protein inhibitory PET/CT changed TNM staging in almost 50% of the cases 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, even in those patients with aggressive disease, the use of CXCR4-targeted PET/CT should be omitted and cannot replace current standard imaging. In this regard, a recent study demonstrating that fibroblast activation protein inhibitory PET/CT may provide an additional benefit, in particular, for PDAC and HCC 16 . Those considerations are further fueled by a recent report exclusively investigating PDAC, also demonstrating that fibroblast activation protein inhibitory PET/CT changed TNM staging in almost 50% of the cases 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition parameters were as follows: 2 to 3 minutes per bed position (mCT 64)/continuous bed motion at 1.1 mm/s (mCT 128); 3 iterations, subsets 24 (mCT 64)/21 (mCT 128); matrix, 200 × 200; Gaussian filter, 2.0 mm. Low-dose CT scans were acquired for attenuation correction (tube voltage, 120 kV; tube current modulation, reference 35 mAs; pitch, 0.8; collimation, 64/128 × 0.6 mm; reconstructed axial slice thickness, 3.0–5.0 mm) 13,16 …”
Section: Methodsmentioning
confidence: 99%
“…One hour after tracer injection, whole-body scans covered the vertex of the skull to the thighs. Low-dose CTs were also performed for anatomical coregistration and attenuation correction 23 . Reconstruction of PET images included corrections for CT-based attenuation, random events, and scatter 16 …”
Section: Methodsmentioning
confidence: 99%
“…1,2 Indeed, this was in line with the expectations of colleagues in the field who have explored the comparable utility of 68 Ga-FAPI PET/CT in the oncologic field generally, as well as for tumors of biliary origin specifically. [3][4][5][6][7][8][9] According to Dendl et al, among others, the explanation could be found in the relatively unique tumor microenvironment of the major cholangiocarcinoma subtypes and the associated abundance of desmoplastic reactions and cancer-associated fibroblasts. 10,11 This, combined with FAPI's significantly lower background (liver) uptake, results in excellent target-to-background ratios and, as a result, improved sensitivity for not only the primary tumor, but also metastatic nodal and distant carcinomatosis.…”
Section: Figurementioning
confidence: 99%